THE LEARNERS’ PERCEPTION OF PROBLEM-BASED LEARNING EXPERIENCE IN SEMINAR ON ELT CLASS - Santi Susanti (Journal of English Education Program (JEEP), 2014)
This paper is a descriptive survey study that aims at investigating the learners’ perception of problem-based learning experience in Seminar on ELT Class. Choosing of approach in learning English is very important because it can influence successful language learning. One of appropriate approaches which makes the students be active and productive learners is learner-centered approach (O’Banion (1997, p. 47) as cited in Bista (2000, p. 114), problem-based learning is one of methods from learner-centered approach that is very effective to make the students be active and productive learners because toward this method the students have to solve the problem based on real world so that it can train the students to think critically (Lepinski, 2005, p. 1). The writer gave the students a questionnaire. After distributing that questionnaire, the writer conducted interview. The findings showed that the students can explore their knowledge because toward problem-based learning the students have to search appropriate information to get solution of the problem. The students can increase their skill, such as critical thinking because the students have to think critically to solve the problem based on real world. The students can learn to work together and independently so that the students can share their knowledge. Problem-based learning is one of methods can increase students’ critical thinking besides the students can learn collaboratively and independently. Lecturers should choose appropriate method to reach the purpose of learning, particularly in student-centered learning.Key words : learners, perception, problem-based learning